DISPUTING IRRATIONAL BELIEFS SEBAGAI STRATEGI MENGURANGI PERILAKU PEOPLE-PLEASING PADA MAHASISWA - Putri Kusuma, Andini; Syahvira Amalie Chusna Assa’adah; Annisa Putri Rahmasari; Prasetya Koswara; Mila Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
People-pleasing behavior generally occurs among students due to various factors such as wanting to make everyone happy, fear of disappointing others, and so on. This study aims to identify types of irrational beliefs, as well as changes in irrational beliefs to more rational or adaptive ones using the DIBs technique. This study uses a qualitative method with a literature research approach, where the researcher collects data by searching journal articles and other reading materials obtained from Google Scholar and other databases limited to the last 10 years. Thus, the results show that the DIBs technique can help individuals make decisions based on personal values, appreciate themselves, and build more authentic relationships without fear of losing social acceptance.